Ventral Bulbar Augmentation: A New Technical Modification of Oral Mucosa Graft Urethroplasty for Stricture of the Proximal Bulbar Urethra - Dalela, Divakar; Sinha, Rahul Janak; Sankhwar, Satya Narayan; Singh, Vishwajeet (Urology Journal, 2010)
Purpose: Complication rates with ventral onlay technique of oral mucosa graft urethroplasty have been attributed to the poor ventral support for the graft. We herein describe a new technique which overcomes these problems and also discuss the short-term follow-up.Materials and Methods: In a prospective study conducted between January 2006 and June 2008, 13 patients with proximal stricture of the bulbar urethra underwent ventral bulbar augmentation. In this technique, the graft was sutured only to the bulbar urethra and the rest of spongiosal tissue was closedsuperficially. Longitudinal incisions were given in the partial depth of the bulb, adjacent to the suture line and were sutured together over the first suture line.Results: The mean follow-up period was 16.4 months (range, 6 to 30 months). Two of the patients developed restricture; one at the proximal anastomosis of the graft with native urethra and one at the distal anastomosis. Remaining 11patients have satisfactory postoperative uroflow rates and are doing well. The success rate at the last follow-up was 84.6%.Conclusion: This technique exploits the local bulbar anatomy by successfullymoving the lateral bulbar tissue medially, below the ventrally placed mucosal graft. This results in a thicker ventral bulbar platform which provides enhanced support to the graft.